Physical activity, sedentary behavior and screen time in young toddlers (1–2 years old) attending Spanish ECEC institutions - Vega-Perona, Herminia; Filenko, Nataliya; Gertrúdix-Barrio, Felipe; Azorín-Delegido, José Manuel; Martínez-Bello, Daniel A.; Bernabé-Villodre, María del Mar; Martínez-Bello, Vladimir E. (Frontiers in Education, 2026)
ObjectivesThis study was designed with three primary objectives: (a) to evaluate the levels of physical activity (PA) and sedentary behavior (SB) in toddlers during the school day at ECEC institutions in Spain; (b) to establish the rate of adherence to specific recommendations for total physical activity (TPA), moderate-to-vigorous physical activity (MVPA), sleep, and screen time; and (c) to characterize the relationship between individual and socioenvironmental correlates and toddlers’ TPA, light physical activity (LPA), MVPA, and SB during the school day.MethodsThis study recruited 264 toddlers (14–23 months) via convenience sampling from public ECEC institutions across three cities. PA was quantified using ActiGraph accelerometry. Sleep behavior was evaluated using the Spanish version of the Brief Infant Sleep Questionnaire (BISQ-E), which was completed by parents. Parents reported their toddler’s average screen time.Results(a) ECEC settings significantly contribute to young children achieving daily TPA recommendations (72%), despite high sedentary time (69%) during school hours. (b) Age positively correlated with LPA (β = 0.003, 95% confidence interval (CI) [CI 0.001, 0.005], p < 0.006), MVPA (β = 0.002, 95% CI [0.000, 0.003], p = 0.004]), and TPA (β = −0.005, 95% CI [0.002, 0.008], p = 0.001) and inversely with SB (β = −0.005, 95% CI [0.0082, 0.002], p = 0.001). (c) No associations were found for gender, BMI, or other personal and social factors with any PA/SB variables. (d) Most young children (64%) exceeded screen time recommendations, while sleep guidelines were largely met (81% adherence); however, no association was between these variables and PA and SB were found. (e) After ECEC hours, unstructured outdoor recreation was strongly preferred over structured activities, and visiting a park at least three times per week was associated with MVPA (β = −0.007, 95% CI [−0.015, 0.001], p = 0.05).ConclusionParents need to be aware of their influence on children’s media habits, and ECEC settings should develop strategies to reduce excessive screen time. A balanced approach to PA, reduced sedentary time, and limited screen exposure—alongside healthy sleep habits supported by such routines—is consistently linked in emerging evidence to better early childhood wellbeing.